The effects of a - tocopherol and verapamil on mucosal functions after gut ischemia / reperfusion* - Mahmut Can YAĞMURDUR; Arif ÖZDEMİR and Ahmet ÖZENÇ and Kamer KILINÇ (Turkish Journal of Gastroenterology, 2019)
-